2024
DOI: 10.1113/jp284041
|View full text |Cite
|
Sign up to set email alerts
|

Dietary sodium alters aldosterone's effect on renal sodium transporter expression and distal convoluted tubule remodelling

Stephanie M. Mutchler,
Mahpara Hasan,
Carolyn P. Murphy
et al.

Abstract: Aldosterone is responsible for maintaining volume and potassium homeostasis. Although high salt consumption should suppress aldosterone production, individuals with hyperaldosteronism lose this regulation, leading to a state of high aldosterone despite dietary sodium consumption. The present study examines the effects of elevated aldosterone, with or without high salt consumption, on the expression of key Na+ transporters and remodelling in the distal nephron. Epithelial sodium channel (ENaC) α‐subunit express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…In previous studies, we showed that chronic treatment of salt and aldosterone induces blood pressure elevations secondary to renal tubular remodeling. 40 However, we found that plasma aldosterone levels do not correlate with SSBP in humans. 35 In the current studies, we demonstrate that changes in both plasma and urine cortisol correlate with human SSBP ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In previous studies, we showed that chronic treatment of salt and aldosterone induces blood pressure elevations secondary to renal tubular remodeling. 40 However, we found that plasma aldosterone levels do not correlate with SSBP in humans. 35 In the current studies, we demonstrate that changes in both plasma and urine cortisol correlate with human SSBP ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 56%
“…39 We demonstrated previously the essential role of APC SGK1 in SSBP. 8,15 Whereas the role of SGK1 activation downstream of MR activation by aldosterone has been extensively studied in chronic salt-induced hypertension secondary to renal perturbations, 40 the mechanism of SGK1 activation in the context of acute blood pressure changes according to salt-intake (SSBP) has not been studied. Here we show that myeloid APCs lack MR expression but instead, we demonstrate high levels of GR expression in these cells (Figure 1).…”
Section: Discussionmentioning
confidence: 99%